Neural basis of new clinical vestibular tests: otolithic neural responses to sound and vibration. (May 2014) - Curthoys, Ian S; Vulovic, Vedran; Burgess, Ann M; Manzari, Leonardo; Sokolic, Ljiljana; Pogson, Jacob; Robins, Mike; Mezey, Laura E; Goonetilleke, Samanthi; Cornell, Elaine D; MacDougall, Hamish G
Summary Extracellular single neuron recording and labelling studies of primary vestibular afferents in Scarpa's ganglion have shown that guinea‐pig otolithic afferents with irregular resting discharge are preferentially activated by 500 Hz bone‐conducted vibration (BCV) and many also by 500 Hz air‐conducted sound (ACS) at low threshold and high sensitivity. Very few afferent neurons from any semicircular canal are activated by these stimuli and then only at high intensity. Tracing the origin of the activated neurons shows that these sensitive otolithic afferents originate mainly from a specialized region, the striola, of both the utricular and saccular maculae. This same 500 Hz BCV elicits vestibular‐dependent eye movements in alert guinea‐pigs and in healthy humans. These stimuli evoke myogenic potentials, vestibular‐evoked myogenic potentials (VEMPs), which are used to test the function of the utricular and saccular maculae in human patients. Although utricular and saccular afferents can both be activated by BCV and ACS, the differential projection of utricular and saccular afferents to different muscle groups allows for differentiation of the function of these two sensory regions. The basic neural data support the conclusion that in human patients in response to brief 500 Hz BCV delivered to Fz (the midline of the forehead at the hairline), the cervical VEMP indicates predominantly saccular function and the ocular VEMP indicates predominantly utricular function. The neural, anatomical and behavioural evidence underpins clinical tests of otolith function in humans using sound and vibration.